(3OjhGf HhQj Hf CjhHs - (3eLO GdOjf CHhSYjO HhQj Hf GjhH Hf TGPj Hf eQhGf,J (B579 (3g` s ((3eMSf Hf Ydj Hf eMeO Hf GdMSjf s)
(3ChdgG (B:s
(3Ndb Gdghi OGA HZjQ OhGA aYdjdg CHOkG HZjQ TaGA s
(3BNQgG (B:s
(3hEfj dCSJTaj ef GdHjf HGdQOi hMSHc OGA Cf JQi GdehJ TGajG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GfXQgG eY GdMSf GdUQjM ddUaOjs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B56s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B52 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B780s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs